Postural symmetry evaluation using phase approximations of the follow-up CoP trajectories. Issue 1 (20th May 2021) - Łukaszewicz, Tomasz; Kidoń, Zenon; Kania, Dariusz; Pethe-Kania, Krystyna
Abstract: This paper presents a method of postural symmetry evaluation implementing the so-called follow-up posturography. The method boils down to the assessment of similarity of the phase approximation of the counter-clockwise follow-up CoP (Center of Pressure) trajectory and the mirror image against the y-axis of the phase approximation corresponding to the clockwise follow-up CoP trajectory. The usability of the presented approach was tested on the data collected in the group of 30 patients rehabilitated after total hip arthroplasty. The observed difference between the values of the proposed postural symmetry coefficient obtained at the end and at the beginning of the rehabilitation program was statistically significant ( p < 0.001). These values, however, were not significantly correlated with the values of postural symmetry coefficients computed in static posturography. Lack of significant correlations between the coefficients supports the reasoning that the new postural symmetry evaluation method quantifies symmetry of posture in terms of dynamic mechanisms, which are not manifested in the case of static posturography. As a major advantage of the herein discussed approach one can distinguish its potential to evaluate postural symmetry in dynamic conditions using relatively inexpensive single-plate posturographic platform.